Development and Efficacy of Child’s Holistic, Individualized Learning and Development Program for Children with Autism - Gana, Raul; Vargas, Marie Ann (Journal of Interdisciplinary Perspectives, 2024)
The primary objective of treating Autism Spectrum Disorder (ASD) is to alleviate symptoms that might disrupt everyday functioning and overall well-being. With this aim in mind, this research sought to highlight the benefits of employing the Child's Holistic, Individualized Learning and Development (CHILD.) Program as a therapeutic approach to enhance the quality of life for children with ASD. Utilizing a mixed methods research approach, the study was conducted at a child learning and development center, involving a cohort of 20 student participants. The researcher employed the Developmental Assessment of Young Children-Second Edition (DAYC-2) to gather data. From the significant findings of the study, it is inferred that the Child's Holistic, Individualized Learning, and Development Program effectively enhances the behavior of children diagnosed with ASD. Additionally, the locally developed program emerges as a credible and effective psychological intervention, presenting considerable potential for improving the skills and conduct of children with ASD. These findings emphasize the significance of personalized interventions to meet the varied needs of individuals with ASD, offering promising avenues for future research and practical implementation in clinical settings.